Innovation of Political Policy Based on Community Development in Handling Covid-19 - Elyta, Elyta; Jamaliah, Jamaliah; Ira Patriani; Laras Putri Olifiani; Syarifah Nurma Afhiani; Saiman Pakpahan (International Journal of Education, Vocational and Social Science, 2022)
In March 2020, World Health Organization states that Covid-19 is an ongoing global pandemic where the disease has claimed thousands of human lives worldwide in a short period. This problem has an impact on almost all countries in the world and all lines of state life, including those related to political policies. This paper aims to analyze the innovation of political policy based on community development in handling Covid-19. This paper uses descriptive qualitative research with literature study methods related to political policies based on community development in the Covid-19 pandemic in Indonesia. The results and discussions of this research have been carried out the innovation of political policy based on community development in handling Covid-19. First, the political policy in health protocol based on community development. Second, the political policy in distribution of welfare based on community development. According to the findings of this study, in dealing the impact of Covid-19, the political policy and community development with active participation have been carried out optimally in Indonesia. This shows the Indonesia government's commitment to global health.